Formation of Priests: Assessing the Past, Reflecting on the Present, Imagining the Future - Zollner, Hans (Razón y fe, 2019)
All formation to the priesthood —initial and ongoing— requires clarity, creativity and perseverance. It does not end when new guidelines for formation are received, developed and promulgated —as in the case of the Ratio fundamentalis of 2016, the framework by which the Church has been guided since that year. The next step in the process —that is, the elaboration and revision of national guidelines for priestly formation by Episcopal Conferences (and to some extent congregations and religious orders), developing what the Ratio fundamentalis indicates— will not be completed until appropriate structures are established and formators are prepared accordingly. Dioceses and religious orders need formators sufficiently prepared for their task. Just as many years and money are invested in the formation of professors in seminaries or faculties, so should be invested in the formation of rectors, spiritual parents and other formators, those who accompany the human and spiritual processes in an important phase of young people’s lives so that young people can better fulfill the excellent choice and vocation of being a priest of Jesus Christ.
Keywords: priesthood; initial and ongoing formation; accompaniment; discernment; human and spiritual formation